A Randomized Controlled Study Comparing Albumin-Enriched Platelet-Rich Fibrin and Conventional Platelet-Rich Fibrin for the Treatment of Intrabony Defects - Sharmila Kumari; Amit Kumar Sharma; Mysore Kantharaja Setty Sunil; Sri Krishna Koppula; Sunil Sharma (Journal of Pharmacy and Bioallied Sciences)
Background: The treatment of intrabony defects (IBDs) is a significant challenge in periodontal therapy, with regenerative approaches like platelet concentrates showing promising outcomes. Materials and Methods: A randomized controlled study was conducted on 20 IBDs from patients who met the inclusion criteria. After Phase I therapy, the defects were randomly assigned to two groups: Group I: Treated with open-flap debridement (OFD) and albumin platelet-rich fibrin (Alb-PRF), Group II: Treated with OFD and PRF. Clinical parameters, including plaque index (PI), bleeding on probing (BOP), probing pocket depth (PPD), and clinical attachment level (CAL), were recorded at baseline and one month postoperatively. Alb-PRF was prepared by centrifuging blood samples at 2,700 rpm for 12 min, collecting the liquid-phase PRF, heating the platelet–poor plasma at 75°C, cooling it, and mixing it with the buffy coat. Results: Both groups showed significant improvement in clinical parameters after one month. In Group I, the mean PPD reduction was 3.2 mm, and CAL gain was 2.8 mm, while in Group II, PPD reduction was 2.9 mm, and CAL gain was 2.5 mm. The reduction in BOP was 50% in Group I and 45% in Group II. PI improvement was similar across groups. Alb-PRF demonstrated a marginally better performance in all clinical parameters compared to PRF alone. Conclusion: Alb-PRF, as an adjunct to OFD, showed better outcomes in reducing PPD and gaining CAL compared to PRF. The results suggest that Alb-PRF may provide a superior regenerative effect in managing IBDs over a short-term period.